Cranial floor fracture: A growing orbital roof fracture with encephalocele – Case Report. (January 2021) - You, Yuchen; Romero, Javier; Diaz, Graal; Herman, James; Siu, Alan; Evans, Robin
Highlights: Orbital roof fractures are among the rarest of craniofacial fractures. Detailed craniofacial examination and high-resolution CT imaging is necessary for diagnosis. A challenging aspect of the fractures is their "growing" nature. A growing encephalocele can complicate the treatment of orbital roof fractures. Orbital roof fractures can become progressively worse secondary to brain swelling. Abstract: Orbital roof fractures are among the rarest of craniofacial fractures. The mechanism of injury is typically a high-impact blunt force vector directly to the orbit or forehead. Most patients are males between 20 and 40 years old, involved in motor vehicle accidents. Although most orbital roof fractures are managed conservatively, there is a significant risk of ophthalmologic and neurologic complications. Detailed craniofacial examination and high-resolution CT imaging is necessary for diagnosis. A multidisciplinary team approach is required for these challenging fractures.